Behavioral sensitivity to broadband binaural localization cues in the ferret. - Keating, P; Nodal, F; Gananandan, K; Schulz, A; King, A (2013)
Although the ferret has become an important model species for studying both fundamental and clinical aspects of spatial hearing, previous behavioral work has focused on studies of sound localization and spatial release from masking in the free field. This makes it difficult to tease apart the role played by different spatial cues. In humans and other species, interaural time differences (ITDs) and interaural level differences (ILDs) play a critical role in sound localization in the azimuthal plane and also facilitate sound source separation in noisy environments. In this study, we used a range of broadband noise stimuli presented via customized earphones to measure ITD and ILD sensitivity in the ferret. Our behavioral data show that ferrets are extremely sensitive to changes in either binaural cue, with levels of performance approximating that found in humans. The measured thresholds were relatively stable despite extensive and prolonged (>16 weeks) testing on ITD and ILD tasks with broadband stimuli. For both cues, sensitivity was reduced at shorter durations. In addition, subtle effects of changing the stimulus envelope were observed on ITD, but not ILD, thresholds. Sensitivity to these cues also differed in other ways. Whereas ILD sensitivity was unaffected by changes in average binaural level or interaural correlation, the same manipulations produced much larger effects on ITD sensitivity, with thresholds declining when either of these parameters was reduced. The binaural sensitivity measured in this study can largely account for the ability of ferrets to localize broadband stimuli in the azimuthal plane. Our results are also broadly consistent with data from humans and confirm the ferret as an excellent experimental model for studying spatial hearing.